The Application of Collaborative Learning Technique of Learning Cell On Cell Materials To The Learning Outcomes and The Students’ Collaboration Character - Mulyaningsih, Erlina; Utami, Nur Rahayu (FMIPA UNNES, 2020)
Learning activities implemented in XI MIPA Class of MAN 1 Semarang tend to be Teacher Centered Learning, so students were passive during the learning process, it causes the achievement of student learning outcomes is not optimal and almost all students seem to find difficulties to collaboration with each other during the learning process. This research aims to determine the effect of the application of collaborative learning models of learning cell techniques to the learning outcomes and the students’ collaboration character on cell material. This research was conducted in MAN 1 Semarang, in the Odd Semester of the 2019/2020 Academic Year. This research is a quasi experimental research design, with Posttest Only Control Group Design. The population used in this research were all students of XI MIPA Class in Odd Semester MAN 1 Semarang in Academic Year 2019/2020 which consisting of 6 classes. The research sample was determined by purposive sampling, so Class XI MIPA 6 was choosen as a control class and Class XI MIPA 4 as an experimental class. Data collection was done by documentation, test, questionnaire, and observation methods. The results of the data analysis showed the t test toward the learning outcomes (posttest scores) obtained that Sig. = 0,008. Because, Sig. (2-tailed) <0,05 then H0 was rejected and Ha was accepted, which means that there were significant differences in student learning outcomes between the experimental class and the control class. The percentage of classical completeness of the experimental class> 80% was 83,3%, while the control class <80% was 61,1%. Based on the results of the analysis of student collaboration character questionnaire it is known that the character of student collaboration in the experimental class> 80% with good and very good criteria reaching 91,7%. Based on this description, it was concluded that the application of collaborative learning models of learning cell techniques has a positive effect on learning outcomes and the character of student collaboration.